Pengaruh Emic View Terhadap Penetapan Kelayakan Lingkungan Rencana Pembangunan Tenaga Listrik Jawa Bali - Endang Susilowati; Sukriyah Kustanti Moerad; Zaenal Arifin (Jurnal Sosial Humaniora, 2025)
Based on the official calculation of power supply, the island of Bali requires the increasing of electric power to support their tourism sectors. The survey's results showed that social-environmental feasibility has met the requirements of Environmental Ministry’s Regulation (no.16, 2012). The assessments of the environmental documents, however, did not fulfill one of ten criteria and that is an emic view especially from the religion communities. As a result, the plan could not be done. This paper intends to give an in-depth analysis of how religion communities try to conceive the governmental planning as a breaking of the religion’s law.